Interaction of nanoparticles and reactive oxygen species and their impact on macromolecules and plant production - Sina Fallah; Elham Yusefi-Tanha; Jose R. Peralta-Videa (Plant Nano Biology)
Nanoparticles (NPs) have emerged as a potent tool for enhancing crop growth and improving agricultural output in the face of global population expansion. However, their application can induce an oxidative state in plants, impacting crop yield. This review evaluates the impact of NPs on the production of reactive oxygen species (ROS), macromolecules, and overall plant performance. Primarily, one of their key effects is the induction of oxidative stress in plants, which alters cellular function and defense mechanisms. Excessive ROS can harm cellular components resulting in cell death. Thus, preserving a delicate equilibrium between ROS production and scavenging is pivotal for cellular redox status. Although high NP concentrations can be detrimental, lower levels can contribute positively to cellular functions and signaling by generating low levels of ROS. Consequently, it is crucial to employ appropriate nanoparticle concentrations to uphold this balance and enhance plant productivity.